Polyethylene-based resin multilayer foam sheet, backing paper for glass plate, and method for producing polyethylene-based resin multilayer foam sheet

By adopting a multi-layer structure design in the polyvinyl resin foam sheet, the problem of low molecular weight component transfer is solved by using the antistatic agent in the intermediate layer and the polystyrene resin in the surface layer, and the excellent operability and pollution resistance of the foam sheet are achieved.

CN115666926BActive Publication Date: 2025-04-29JSP CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180040447.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-05
Filing Date
2021-05-28
Publication Date
2025-04-29
Estimated Expiration
2041-05-28

AI Technical Summary

Technical Problem

After using antistatic agents in existing polyvinyl resin foam sheets, there is still a problem of transferring low molecular weight components to packaging products, which affects their operability and anti-pollution properties.

Method used

A polyvinyl resin foam sheet with a multi-layer structure includes a foam layer and a resin layer on both sides of the foam layer. The resin layer is composed of a surface layer, an intermediate layer and a foam layer. The intermediate layer contains a polymer antistatic agent, while the surface layer basically does not contain an antistatic agent, and the polystyrene resin content is between 3-35% by weight.

Benefits of technology

The foam sheet is excellent antistatic, sliding, anti-adhesion and stiffness, while significantly reducing the transfer of low molecular weight components to packaging products and improving its anti-pollution performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 707623
    Figure 707623
  • Figure DEST_PATH_IMAGE001
    Figure DEST_PATH_IMAGE001
  • Figure DEST_PATH_IMAGE003
    Figure DEST_PATH_IMAGE003
Patent Text Reader

Abstract

The surface resistivity of the multilayer foam sheet is 1×10 13 Ω or less, and having a foam layer and a resin layer laminated on both surfaces of the foam layer. The resin layers each have a multilayer structure formed by a surface layer and an intermediate layer located between the surface layer and the foam layer. The foam layer includes a polyethylene resin PE2. The intermediate layer is composed of an antistatic mixture containing a polyethylene resin PE3 and a polymer antistatic agent. The surface layer is composed of a mixed resin containing a polyethylene resin PE4 and a polystyrene-based resin, and is substantially free of a polymer antistatic agent. The polystyrene-based resin content of the mixed resin is 3-35% by weight.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a multilayer foam sheet, and more particularly to a polyethylene-based resin multilayer foam sheet which can be used as a backing paper and packaging material for electronic devices, etc., and to a method for producing the same. Background Art

[0002] Polyethylene-based resin foam sheets are used in the fields of cushioning materials, packaging materials, etc. because they have both flexibility and cushioning properties. However, polyethylene-based resin foam sheets (hereinafter also referred to simply as foam sheets) have problems of easily generating static electricity and causing dust to easily adhere to products packaged therewith due to static electricity. Therefore, foam sheets imparted with antistatic properties are used for applications that do not like the generation of static electricity and the adhesion of dust.

[0003] As the foam sheet material endowed with antistatic properties, the foam sheet material containing polymer antistatic agent is known. For example, patent document 1 discloses a multilayer foam sheet material, wherein a surface layer consisting of polyolefin-based resin is laminated on one or both sides of a polyolefin-based resin foam layer, and wherein the surface layer contains a polymer antistatic agent. Because the surface layer contains a polymer antistatic agent, the foam sheet material has excellent antistatic properties. Therefore, compared with the foam sheet material using a surfactant as an antistatic agent, such a foam sheet material significantly reduces the amount of pollution caused by organic substances such as low molecular weight components being transferred to the products packaged therewith. Therefore, such a foam sheet material is suitable for being used as a backing paper or packaging material for glass plates such as liquid crystal panels and electronic devices waiting to be packaged products that do not like dust and low molecular weight components to adhere to their surfaces.

[0004] On the other hand, when used as a liner for a glass plate, etc., the foam sheet needs to be excellent in handleability. Excellent handleability is a general term for excellent slidability, anti-blocking properties, and rigidity (or stiffness) of the foam sheet.

[0005] As used herein, "excellent slidability" is intended to mean that the friction generated between the foam sheet and the article packaged therewith is small, so that, for example, when glass is packaged in a manner in which the foam sheet is inserted between them as a backing paper for glass plates, transportation and overlapping of the foam sheet on the glass plates can be carried out smoothly.

[0006] "Blocking" is a phenomenon in which, for example, when foam sheets are cut into a desired size and stacked, foam sheets adhere to each other, making it impossible to smoothly take out the foam sheets one by one. "Anti-blocking property" refers to a property capable of preventing blocking from occurring.

[0007] In addition, "excellent rigidity" means that the amount of horizontal sagging when the foam sheet is cantilevered is small. When the foam sheet is used as a backing paper, the work of removing the foam sheet sandwiched between the glass plates is performed by vacuum suction. At this time, if the amount of horizontal sagging is small, the backing paper can be easily removed. On the other hand, if the amount of horizontal sagging of the cantilevered foam sheet is large, the efficiency of the removal operation is significantly reduced. Therefore, the foam sheet used as the backing paper needs to have good rigidity.

[0008] As a foam sheet having both excellent sliding properties and excellent rigidity, Patent Document 2 discloses a foam sheet having a three-layer structure having a polyethylene-based resin foam layer and an antistatic layer provided on both sides of the foam layer, and the antistatic layer contains a polyethylene-based resin, a polystyrene-based resin and a polymer antistatic agent.

[0009] Prior art documents

[0010] [Patent Document]

[0011] [Patent Document 1] Japanese Unexamined Patent Publication No. JP2008-308695A;

[0012] [Patent Document 2] U.S. Patent Application Publication No. US201600311202A. Summary of the invention

[0013] Problems to be solved by the present invention:

[0014] However, in recent years, there has been a demand for a foam sheet that is less likely to contaminate an article packaged therewith than the foam sheets disclosed in Patent Documents 1 and 2. That is, even in a foam sheet using the above-mentioned polymer antistatic agent, there is a case where a trace amount of low molecular weight components contained in the polymer antistatic agent itself transfers to an article packaged therewith and contaminates the article packaged therewith. Therefore, there is a demand for a polyethylene-based resin foam sheet that is not only excellent in handleability but also greatly reduces the transfer of low molecular weight components to an article packaged therewith.

[0015] An object of the present invention is to provide an antistatic polyethylene-based resin multilayer foam sheet having excellent rigidity, excellent slidability, excellent antistatic properties, and capable of significantly reducing the transfer of low molecular weight components to products packaged therewith while maintaining the excellent cushioning properties inherent to the polyethylene-based resin foam sheet, and to provide a method for producing the same.

[0016] Means of solving the problem:

[0017] According to one aspect of the present invention, there is provided a multilayer foam sheet as follows:

[0018] [1] A polyethylene-based resin multilayer foam sheet comprising a foam layer and a resin layer provided on each of both sides of the foam layer,

[0019] the resin layer has a multilayer structure including a surface layer located on the outermost surface side of the multilayer foam sheet and an intermediate layer located between the surface layer and the foam layer,

[0020] The foam layer includes polyethylene resin PE2,

[0021] The middle layer is composed of an antistatic resin composition containing a polyethylene resin PE3 and a polymer antistatic agent.

[0022] in

[0023] The surface layer is composed of a mixed resin containing polyethylene-based resin PE4 and polystyrene-based resin.

[0024] The mixed resin is substantially free of polymeric antistatic agents,

[0025] The content of the polystyrene-based resin in the mixed resin is 3 wt % or more and 35 wt % or less, and

[0026] The surface resistivity of the polyethylene-based resin multilayer foam sheet is 1×10 13 Ω or less.

[0027] [2] The polyethylene-based resin multi-layer foam sheet according to the above-mentioned [1], wherein a weight ratio of the polystyrene-based resin to the polyethylene-based resin PE4 in the mixed resin is 0.03 or more and 0.4 or less.

[0028] [3] The polyethylene-based resin multi-layer foam sheet according to the above-mentioned [1] or [2], wherein the content of the polystyrene-based resin in the mixed resin is 3% by weight or more and 12% by weight or less.

[0029] [4] The polyethylene-based resin multilayer foam sheet according to any one of [1] to [3] above, wherein the content of the polymer antistatic agent in the antistatic resin composition is 5 wt% or more and 25 wt% or less based on the total weight of the polyethylene-based resin PE3 and the polymer antistatic agent.

[0030] [5] The polyethylene-based resin multilayer foam sheet according to any one of [1] to [4] above, wherein the polymer antistatic agent is an ionomer resin.

[0031] [6] The polyethylene-based resin multilayer foam sheet according to the above [5], wherein the antistatic resin composition contains polyalkylene glycol, and the content of the polyalkylene glycol is 0.3-6 parts by weight based on 100 parts by weight in total of the polyethylene-based resin PE3 and the polymer antistatic agent.

[0032] [7] The polyethylene-based resin multilayer foam sheet according to any one of [1] to [6] above, wherein each 1 m 2 The content of the polymer antistatic agent in the intermediate layer is 0.15 g or more and 2 g or less, and the quantitative B4 [g / m 2 ] and the content of the polymer antistatic agent A [g / m 2 ] ratio (B4 / A) is greater than 1 and less than 30.

[0033] [8] The polyethylene-based resin multilayer foam sheet according to any one of [1] to [7] above, wherein the basis weight B4 of the surface layer is 0.5 g / m 2 Above and 10 g / m 2 the following.

[0034] [9] The polyethylene-based resin multi-layer foam sheet according to any one of [1] to [8] above, wherein the polyethylene-based resin PE2 is a low-density polyethylene, and the polyethylene-based resin PE3 is a low-density polyethylene.

[0035]

[10] The polyethylene-based resin multilayer foam sheet according to any one of [1] to [9] above, wherein the polyethylene-based resin PE2 has a melt flow rate of 0.1 g / 10 min or more and 1.5 g / 10 min or less at a temperature of 190° C. and a load of 2.16 kg.

[0036]

[11] The polyethylene-based resin multilayer foam sheet according to any one of [1] to

[10] above, which has a closed cell content of 40% or more.

[0037] In another aspect, the present invention provides:

[0038]

[12] Use of the polyethylene-based resin multilayer foam sheet according to any one of 1 to 11 above as a spacer paper for a glass plate.

[0039] In a further aspect, the present invention provides:

[0040]

[13] A method for producing a polyethylene-based resin multilayer foam sheet having a surface resistivity of 1×10 13Ω or less and having a multilayer structure in which a first surface layer, a first intermediate layer, a foam layer, a second intermediate layer, and a second surface layer are laminated in this order, the method comprising the steps of:

[0041] providing a foamable melt M2 for forming the foam layer containing a polyethylene-based resin PE2 and a physical foaming agent, a melt M3 composed of an antistatic resin composition containing a polyethylene-based resin PE3 and a polymer antistatic agent for forming the first intermediate layer and the second intermediate layer, and a melt M4 composed of a mixed resin containing a polyethylene-based resin PE4 and a polystyrene-based resin and not containing a polymer antistatic agent for forming the first surface layer and the second surface layer,

[0042] laminating the melts M4, M3, M2, M3 and M4 in this order in a mold to form a laminated material, and

[0043] co-extruding the laminated material from the die to expand the foamable melt M2,

[0044] The polystyrene-based resin is contained in the mixed resin composition in an amount of 3 wt % or more and 35 wt % or less based on the weight of the mixed resin composition.

[0045] Effect of the invention:

[0046] The multilayer foam sheet of the present invention has excellent antistatic properties, wherein the surface resistivity is 1×10 12 Ω or less. In addition, in the multilayer foam sheet, since the surface layer covering the intermediate layer does not substantially contain a polymer antistatic agent, the transfer of low molecular weight components and the like to the product packaged therewith is suppressed to an extremely small extent. In addition, since the surface layer contains a specific amount of polystyrene-based resin, the foam sheet is excellent in handling properties (sliding property, anti-blocking property and rigidity). BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 is a schematic cross-sectional view showing one embodiment of the multi-layer foam sheet according to the present invention. DETAILED DESCRIPTION

[0048] The polyethylene-based resin multi-layer foam sheet of the present invention will be described in detail below.

[0049] As in Figure 1As shown in FIG. 1 , the polyethylene-based resin multilayer foam sheet 1 of the present invention (hereinafter also referred to as a multilayer foam sheet or simply as a foam sheet) has a foam layer 2 and a resin layer 5 provided on each of both surfaces of the foam layer 2. Each resin layer 5 has a multilayer structure including a surface layer 4 (hereinafter also referred to as a surface layer) located on the outermost surface side of the multilayer foam sheet 1 and an intermediate layer 3 located between the surface layer 4 and the foam layer 2. That is, in Figure 1 The multilayer foam sheet 1 specifically shown in the figure has a five-layer structure consisting of a resin layer 5 (surface layer 4 / middle layer 3) / foam layer 2 / resin layer 5 (middle layer 3 / surface layer 4). The foam sheet 1 of the present invention is not limited to such a five-layer structure. As long as the gist and effect of the present invention are not adversely affected, a 6-layer structure or a 7-layer structure may be adopted by providing an additional layer (not shown) formed by a polymer (e.g., resin) between the foam layer and one or two resin layers.

[0050] For the sake of brevity, the following description is made about one of the paired resin layers 5, but the description is also applicable to the other resin layers. It should be noted that the two resin layers 5 can have the same or different configurations as long as the requirements described in detail below are met. For example, the type and amount of the resin components and additives and the physical property values ​​such as quantitative of one of the two surface layers 4 can be the same or different from those of the other surface layer.

[0051] As used herein, a numerical range of "from A to B" is intended to include a lower limit "A" and an upper limit "B", and is thus synonymous with "above A and below B."

[0052] It is preferred that the resin layer 5 (surface layer 4 and / or intermediate layer 3) is not foamed (is non-foamed). However, very small bubbles may be present within a range that does not adversely affect the mechanical strength of the obtained foam sheet 1. When the resin layer 5 is non-foamed, the rigidity of the multilayer foam sheet 1 becomes more excellent.

[0053] As will be described below, because the intermediate layer 3 contains a polymer antistatic agent, the multilayer foam sheet 1 of the present invention exhibits excellent antistatic properties, wherein the surface resistivity is 1×10 13 On the other hand, since the surface layer 4 does not contain a polymer antistatic agent, low molecular weight components contained in the polymer antistatic agent are prevented from transferring to the product to be packaged. In addition, since the surface layer 4 contains a specific amount of polystyrene-based resin, the handling properties (sliding property, anti-blocking property, rigidity, etc.) are excellent.

[0054] The following will describe the materials constituting the foam layer 2, the surface layer 4, and the intermediate layer 3. The foam layer 2 is composed of a base polymer containing a polyethylene-based resin PE2, the intermediate layer 3 is composed of an antistatic resin composition containing a polyethylene-based resin PE3 and a polymer antistatic agent (hereinafter also referred to as resin composition R3), and the surface layer 4 is composed of a mixed resin containing a polyethylene-based resin PE4 and a polystyrene-based resin (hereinafter also referred to as mixed resin R4).

[0055] In this specification, polyethylene resins PE2, PE3 and PE4 are each intended to mean a polyethylene resin containing 50 mol % or more, preferably 60 mol % or more, more preferably 70 mol % of an ethylene component. Specific examples of polyethylene resins include low-density polyethylene (LDPE), ethylene-vinyl acetate copolymers (EVA), linear low-density polyethylene (LLDPE), very low-density polyethylene (VLDPE) and mixtures thereof. Low-density polyethylene refers to a polyethylene having a long-chain branched structure and a density of 910 kg / m 3 Over and less than 930 kg / m 3 Linear low-density polyethylene refers to a polyethylene-based resin that is a copolymer of ethylene and an α-olefin having 4 to 8 carbon atoms, which has a substantially linear molecular chain and a density of 910 kg / m 3 Over and less than 930 kg / m 3 ; and high-density polyethylene refers to a polyethylene-based resin that is an ethylene homopolymer or a copolymer of ethylene and an α-olefin having 4 to 8 carbon atoms, and has a density of 930 kg / m 3 above.

[0056] The foam layer 2 is composed of a base polymer containing a polyethylene resin PE2. That is, the foam layer 2 contains a polyethylene resin PE2. Specifically, the content of the polyethylene resin PE2 in the foam layer is 50% by weight or more, preferably 60% by weight or more, more preferably 70% by weight or more, still more preferably 80% by weight or more, and most preferably 90% by weight or more. As used herein, the term "base polymer" is intended to mean any polymer, resin or composition capable of forming a foam having a plurality of cells by extrusion foaming.

[0057] Since low-density polyethylene has excellent foaming properties and produces a multilayer foam sheet with more excellent cushioning properties, it is preferred that the polyethylene-based resin PE2 contains low-density polyethylene in an amount of 50% by weight or more. From this point of view, it is preferred that the polyethylene-based resin PE2 contains low-density polyethylene in an amount of 80% by weight or more, more preferably 90% by weight or more.

[0058] Because of its excellent foaming property, the melt flow rate (MFR) of the polyethylene-based resin PE2 is preferably 0.1-20 g / 10 min, more preferably 0.1-10 g / 10 min, and still more preferably 0.1-5 g / 10 min. The multilayer foam sheet of the present invention is preferably produced by a coextrusion method, and in this case, it is particularly preferred to use a polyethylene-based resin (A) having a melt flow rate (MFR) of 0.1-1.5 g / 10 min. The reason for this will be described in detail in the section on the method for producing the multilayer foam sheet.

[0059] As used herein, the melt flow rate (MFR) of the polyethylene-based resin refers to a melt mass flow rate measured under the conditions of 190° C. and a load of 2.16 kg according to JIS K 7210-1 (2014).

[0060] If necessary, another polymer other than the polyethylene-based resin (e.g., resin and elastomer) may be incorporated into the base polymer containing the polyethylene-based resin PE2 and constituting the foam layer. When such another polymer is blended, the blending amount is preferably 20 parts by weight or less, more preferably 10 parts by weight or less, still more preferably 5 parts by weight or less, particularly preferably 3 parts by weight or less, based on 100 parts by weight of the polyethylene-based resin (PE2) constituting the foam layer.

[0061] Additives such as cell control agents, nucleating agents, antioxidants, heat stabilizers, weathering agents, ultraviolet absorbers, flame retardants, antibacterial agents, shrinkage inhibitors and inorganic fillers may be added to the base polymer constituting the foam layer as long as the objects and effects of the present invention are not adversely affected.

[0062] Next, the material constituting the middle layer 3 will be described. The middle layer is composed of an antistatic resin composition R3 containing a polyethylene resin PE3 and a polymer antistatic agent. That is, the middle layer includes a polyethylene resin PE3 and a polymer antistatic agent. The polyethylene resin PE3 is a main component of the middle layer. Specifically, based on the weight of the middle layer (i.e., the weight of the antistatic resin composition R3), the content of the polyethylene resin is preferably 50% by weight or more, more preferably 60% by weight or more, and even more preferably 70% by weight or more.

[0063] It is preferred that the polyethylene-based resin PE3 used is of the same type as the polyethylene-based resin PE2 constituting the foam layer because of its excellent adhesion to the foam layer. Specifically, low-density polyethylene is preferably used. However, different types of polyethylene-based resins may also be used.

[0064] Since the antistatic resin composition (R3) constituting the intermediate layer contains a polymer antistatic agent, the multilayer foam sheet of the present invention exhibits excellent antistatic properties despite the lamination of the surface layer on the intermediate layer. Specifically, the surface resistivity of the multilayer foam sheet should be 1×10 13 Ω or less, preferably 5×10 12 Ω or less, more preferably 1×10 12 Ω or less, particularly preferably 5×10 11 The lower limit of the surface resistivity is not particularly limited, but is usually 1×10 7 The multi-layer foam sheet having a surface resistivity within such a range is less likely to accumulate static charge and less likely to adhere to dust.

[0065] The surface resistivity of the multilayer foam sheet is a value measured in accordance with JIS K6271 (2001). More specifically, a test piece (length 100 mm×width 100 mm×thickness: thickness of the object to be measured) is first cut out from the multilayer foam sheet to be measured, and allowed to stand for 24 hours in an atmosphere having a temperature of 23° C. and a relative humidity of 50% to condition the test piece. Then a voltage of 500 V is applied to the surface of the test piece in an atmosphere having a temperature of 23° C. and a relative humidity of 50%, and the surface resistivity is measured 1 minute after the start of the voltage application.

[0066] Polymer antistatic agents have a surface resistivity of usually less than 1×10 12 Ω, preferably less than 1×10 11 Ω, more preferably less than 1×10 10 Ω. Specific examples thereof include polyether, polyether ester amide, block copolymer of polyether and polyolefin, and ionomer resin. Among them, block copolymer of polyether and polyolefin and ionomer resin are more preferred, and ionomer resin is particularly preferred.

[0067] The ionomer resin has low surface resistivity, can impart good antistatic properties to the multilayer foam sheet, and further has a low content of low molecular weight components. Therefore, contamination due to the transfer of low molecular weight components to the product to be packaged can be significantly suppressed.

[0068] Compared with foam sheets containing other polymer antistatic agents such as polyether-polyolefin block copolymers, foam sheets containing ionomer resins tend to become inferior in slidability. On the other hand, in the present invention, since the intermediate layer containing ionomer resins is covered with the surface layer described below, the foam sheet containing ionomer resins can prevent the slidability from being reduced.

[0069] Ionomer resins are resins in which the molecules of a copolymer of an olefin and an unsaturated carboxylic acid are crosslinked with metal ions. Examples of olefins include ethylene and propylene. Examples of unsaturated carboxylic acids include acrylic acid, methacrylic acid and maleic acid. Examples of metal ions include lithium, sodium and potassium. Among them, ionomer resins containing potassium as a metal ion, particularly potassium-containing ionomer resins of copolymers of ethylene and unsaturated carboxylic acids, are preferred because they can impart good antistatic properties to the foam sheet.

[0070] The surface resistivity of the ionomer resin is preferably less than 1×10 12 Ω. By using a surface resistivity less than 1×10 12 The antistatic layer is formed by an ionomer resin with a surface resistivity of 1×10 11 Ω or less, more preferably 1×10 10 Ω or less, particularly preferably 1×10 9 Ω or less.

[0071] The surface resistivity of the ionomer resin can be measured by the same method as that of measuring the surface resistivity of the multilayer foam sheet.

[0072] For example, specific examples of the polymer antistatic agent include block copolymers of polyether and polyolefin such as "Perestat 300", "Perestat 230", "Perestat HC250", "Perectron PVH", "PerectronPVL", "Perectron HS" and "Perectron LMP" manufactured by Sanyo Kasei Kogyo Co., Ltd., and ionomer resins commercially available from Mitsui-DuPont Polychemical Co., Ltd under trade names such as "Entila SD100" and "Entila MK400".

[0073] Based on the polyethylene resin PE3 and the polymer antistatic agent of 100 % by weight in total, the content of polymer antistatic agent in antistatic resin composition R3 (i.e. intermediate layer) is preferably 5-25 % by weight, although it depends on the performance of polymer antistatic agent itself.When the content (concentration) of polymer antistatic agent is more than 5 % by weight, the conductive network structure of polymer antistatic agent is stably formed in the intermediate layer, although the laminated surface layer is made on the intermediate layer, antistatic performance is uniformly shown in the whole foam sheet.In addition, when content is below 25 % by weight, the pollution of the product to be packaged caused by the transfer of the low-molecular weight components derived from the polymer antistatic agent can be further reduced.In addition, the reduction of the slipperiness caused by the polymer antistatic agent can be more reliably prevented.Therefore, the lower limit of content is more preferably 7 % by weight, and more preferably 9 % by weight, and the upper limit of content is more preferably 20 % by weight, and more preferably 15 % by weight.

[0074] Every 1m 2 The content A of the polymer antistatic agent in the middle layer is preferably 0.15-2 g / m 2 The content A represents the absolute amount of the polymer antistatic agent contained in the interlayer per unit area.

[0075] When the content A is 0.15g / m 2 When the content A is more than 0.18 g / m 2 , and more preferably 0.19 g / m 2 , particularly preferably 0.2 g / m 2 On the other hand, when the content A is 2g / m 2 When the content A is less than 1.5 g / m2, organic substances such as low molecular weight components in the polymer antistatic agent contained in the intermediate layer 3 are less likely to ooze out to the surface of the surface layer 4. Therefore, the upper limit of the content A is more preferably 1.5 g / m2. 2 , and more preferably 1.0 g / m 2 , particularly preferably 0.8 g / m 2 In order to exhibit a sufficient antistatic effect while maintaining the value of the content A within the above range, it is preferred that the intermediate layer 3 is non-foamed.

[0076] The content A is a value of one of a pair of intermediate layers 3 provided on both sides of the foam layer 2 .

[0077] In the present invention, it is preferred that the surface layer 4 has a weight B4 [g / m 2 ] and every 1 m 2 The content of the polymer antistatic agent in the intermediate layer 3 is A [g / m 2] The ratio B4 / A is 1 to 30. When the ratio is within this range, the balance between the antistatic property and the antifouling property becomes more excellent.

[0078] Ratio B4 / A is the index of the ratio of the weight of the polymer antistatic agent that the quantitative B4 of display surface layer 4 and intermediate layer 3 comprise in its per unit area.In order to suppress the transfer of the low-molecular weight component that is included in the polymer antistatic agent to the goods for use its packaging, preferably reduce the content A of the polymer antistatic agent, or increase the quantitative B4 of the surface layer 4 (to increase the thickness of the surface layer 4).On the other hand, in order to make the foam sheet show enough antistatic properties, preferably increase the content A of the polymer antistatic agent or reduce the quantitative B4 of the surface layer (to reduce the thickness of the surface layer).In foam sheet of the present invention, ratio B4 / A is preferably in the above-mentioned scope, to suppress the transfer of low-molecular weight component and show enough antistatic properties.

[0079] From the viewpoint of achieving both antistatic properties and antifouling properties in a more balanced manner, the lower limit of the ratio B4 / A is preferably 2, more preferably 3, still more preferably 4, while the upper limit of the ratio is preferably 25, more preferably 20, still more preferably 15, particularly preferably 10.

[0080] When an ionomer resin is used as a polymer antistatic agent, polyalkylene glycol is preferably incorporated into the intermediate layer 3, because the ionomer resin can be uniformly dispersed in the intermediate layer, and the foam sheet can therefore exhibit excellent antistatic properties in a stable manner. That is, when the foam sheet is produced by coextrusion, and when the melt to be extruded for forming the intermediate layer (i.e., the molten antistatic resin composition R3) contains polyalkylene glycol, the ionomer resin can be satisfactorily dispersed in the polyethylene-based resin PE3, so that even if the intermediate layer is covered with a surface layer, a multilayer foam sheet with excellent antistatic properties can be obtained.

[0081] Furthermore, the presence of the polyalkylene glycol in the intermediate layer helps to reduce the humidity dependence of the antistatic performance, so that the obtained multilayer foam sheet exhibits good antistatic performance even under low humidity conditions.

[0082] As the polyalkylene glycol, a polyalkylene glycol having an HLB value of 8 or more can be preferably used. Examples of such polyalkylene glycols include polyethylene glycol and polyoxyethylene polyoxypropylene glycol. In addition, two or more polyalkylene glycols can be used in combination. Among them, polyethylene glycol is preferably used because it can stably disperse the ionomer resin in the polyethylene-based resin and can further reduce the humidity dependence of the antistatic performance while enhancing the antistatic performance.

[0083] In the present invention, the HLB value is obtained by the Griffin method using the following equation:

[0084] HLB = 20×Mh / Mw

[0085] Where Mh is the molecular weight of the hydrophilic portion of the hydrophilic compound and Mw is the molecular weight of the entire hydrophilic compound.

[0086] Based on the polyethylene resin PE3 and the polymer antistatic agent totaling 100 weight parts, preferably polyalkylene glycol is included in the antistatic resin composition R3 (i.e., intermediate layer) with the amount of 0.3-8 weight part. When polyethylene glycol is used as polyalkylene glycol, based on the polyethylene resin PE3 and the polymer antistatic agent totaling 100 weight parts, its content is preferably 0.3-6 weight part. Its lower limit is more preferably 0.35 weight part, and is even more preferably 0.4 weight part, and its upper limit is more preferably 5 weight parts, and is even more preferably 3 weight parts, and is particularly preferably 2 weight parts.

[0087] When an ionomer resin is used as an antistatic agent, the weight ratio of the polyalkylene glycol to the ionomer resin is preferably 0.03-0.5 because the ionomer resin can be better dispersed in the polyethylene-based resin. From this point of view, the weight ratio is more preferably 0.04-0.3.

[0088] The antistatic resin composition R3 constituting the intermediate layer may contain, in addition to the polyethylene-based resin PE3 and the polymer antistatic agent, other polymers, additives, etc., as long as the objects and effects of the present invention are not adversely affected.

[0089] Incidentally, preferably antistatic resin composition R3 (i.e. intermediate layer) is substantially free of polystyrene-based resin. More specifically, the content of polystyrene-based resin in antistatic resin composition R3 is preferably below 5 % by weight, more preferably below 3 % by weight, also more preferably below 2 parts by weight, particularly preferably 0. By reducing the content of polystyrene-based resin in antistatic resin composition R3, the closed-cell content of multilayer foam sheet can be further increased, to further improve its rigidity and cushioning properties, and in addition, to develop its recyclability.

[0090] Next, the material constituting the surface layer 4 will be described.

[0091] The surface layer is composed of a mixed resin R4 containing a polyethylene resin PE4 and a polystyrene resin. That is, the surface layer contains polyethylene resin PE4 and polystyrene resin. Polyethylene resin PE4 is the main component of the surface layer. Specifically, based on the weight of the surface layer (i.e., the weight of the resin mixture R4), the content of polyethylene resin PE4 is preferably 50% by weight or more, more preferably 60% by weight or more, and even more preferably 70% by weight or more.

[0092] As the polyethylene-based resin PE4, a polyethylene-based resin exemplified as the polyethylene-based resin PE3 can be used. It is preferred to use a resin of the same kind as the polyethylene-based resin PE3 because the resulting resin layer 5 shows excellent adhesion between its surface layer 4 and the intermediate layer 3. Specifically, the polyethylene-based resin PE4 preferably contains a low-density polyethylene in an amount of 50% by weight or more. In addition, when a linear low-density polyethylene is used as the polyethylene-based resin PE4, the transfer amount of low molecular weight components can be further suppressed. However, different kinds of polyethylene-based resins can also be used.

[0093] The mixed resin R4 does not contain substantially any polymer antistatic agent. Since the surface layer is located on the outermost surface side of the foam sheet and is in direct contact with the product to be packaged therewith, when the mixed resin R4 constituting the surface layer does not contain any polymer antistatic agent, it is possible to prevent low molecular weight components contained in the polymer antistatic agent from contaminating the packaged product due to its transfer. In addition, since the polymer antistatic agent is contained in the intermediate layer, the desired antistatic properties can be exhibited even though the surface layer does not contain any polymer antistatic agent.

[0094] In the present invention, "substantially free of polymer antistatic agent" means that the content of polymer antistatic agent is about 3 wt% or less (including 0) based on the weight of mixed resin R4 (i.e., surface layer). The content is more preferably 1 wt% or less (including 0). In order to suppress the transfer of low molecular weight components, it is particularly preferred that mixed resin R4 does not contain polymer antistatic agent, that is, its content is 0.

[0095] Furthermore, in the multi-layer foam sheet of the present invention, it is preferred that the surface layer substantially does not contain an antistatic agent other than the polymeric antistatic agent. Examples of such an antistatic agent other than the polymeric antistatic agent include surfactants.

[0096] The mixed resin R4 constituting the surface layer 4 of the multilayer foam sheet of the present invention contains a specific amount of polystyrene-based resin (PS). Therefore, the multilayer foam sheet is excellent in sliding property, anti-blocking property and rigidity.

[0097] Examples of polystyrene-based resins include polystyrene (general-purpose polystyrene), rubber-modified polystyrene (impact polystyrene), styrene-α-methylstyrene copolymers, styrene-p-methylstyrene copolymers, styrene-acrylic acid copolymers, styrene-methacrylic acid copolymers, styrene-maleic anhydride copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-methyl acrylate copolymers, styrene-ethyl acrylate copolymers, and styrene-acrylonitrile copolymers. Among them, polystyrene or rubber-modified polystyrene is preferred, and polystyrene is more preferred.

[0098] Based on the weight of mixed resin R4, in mixed resin R4 (i.e. surface layer), the content of polystyrene-based resin is more than 3 % by weight and below 35 % by weight. When the content of polystyrene-based resin in the surface layer is less than 3 % by weight, depending on its application purpose, there is the possibility that the sliding property of foam sheet may be insufficient. In addition, when stacking and storing foam sheet, it is worried that adhesion may occur. In order to further improve the sliding property and anti-adhesion properties of foam sheet, preferably polystyrene-based resin is included in the mixed resin R4 with the amount more than 4% by weight.

[0099] On the other hand, when the content of the polystyrene-based resin exceeds 35% by weight, there is a possibility that the rigidity of the foam sheet may be reduced. In addition, the excellent cushioning properties inherent in the foam sheet may not be maintained. In order to improve the rigidity while maintaining the excellent cushioning properties of the foam sheet, the content of the polystyrene-based resin in the mixed resin R4 is preferably 30% by weight or less, more preferably 25% by weight or less, still more preferably 20% by weight or less, particularly preferably 12% by weight or less, and most preferably 8% by weight or less.

[0100] In the present invention, when the content of polystyrene-based resin in the mixed resin R4 constituting the surface layer 4 is within the above range, rigidity becomes higher as the content decreases. On the other hand, rigidity tends to decrease as the content of polystyrene-based resin increases. The reason why rigidity decreases as the content of polystyrene-based resin (which is a resin with higher rigidity than polyethylene-based resin PE4) increases is unclear, but can be considered as follows. That is, when the foam sheet of the present invention is produced by coextrusion, and when the content of polystyrene-based resin in the mixed resin R4 for forming the surface layer becomes large, the melt viscosity of the melt (i.e. molten mixed resin R4) for forming the surface layer increases, because the fluidity of the polystyrene-based resin molten near the extrusion temperature is lower than the fluidity of the polyethylene-based resin PE4 molten. Therefore, the foamable melt coextruded in the coextrusion die for forming the foam layer generates heat to cause the closed-cell content of the obtained foam layer to decrease. It is inferred that, as a result, the rigidity of the multilayer foam sheet decreases.

[0101] In addition, it is preferred that in the mixed resin R4, the ratio PS(C) / PE(C) of the content of the polystyrene-based resin (PS) (PS(C)) to the content of the polyethylene-based resin PE4 (PE(C)) is 0.03-0.6. The fact that the ratio PS(C) / PE(C) is within this range means that the content of the polystyrene-based resin (PS) is lower than the content of the polyethylene-based resin PE4. When the surface layer 4 contains the polystyrene-based resin in such an amount as to provide a ratio PS(C) / PE(C) within the above range, its rigidity, sliding properties and anti-adhesion properties are further improved. In addition, the thickness recovery properties after the foam sheet is manufactured are improved. In order to maintain good rigidity of the foam sheet, the upper limit of the ratio PS(C) / PE(C) is preferably 0.4, more preferably 0.3, still more preferably 0.2, and particularly preferably 0.1. In addition, in order to improve the sliding properties and anti-adhesion properties of the foam sheet, the lower limit of the ratio PS(C) / PE(C) is more preferably 0.04.

[0102] In order to improve the sliding property of the foam sheet, the tensile strength of the mixed resin R4 constituting the surface layer 4 is preferably 10 MPa or more. The tensile strength can be adjusted by changing the content of the polystyrene-based resin in the mixed resin R4 within the above range.

[0103] The tensile strength of the mixed resin R4 can be measured using a test piece punched into a dumbbell shape No. 1 under the condition of a test speed of 500 mm / min in accordance with JIS K6767 (1999), and a calculated value is adopted.

[0104] The mixed resin R4 preferably contains a compatibilizer for the polyethylene-based resin PE4 and the polystyrene-based resin. Since the compatibilizer can improve the film-forming property of the mixed resin R4, a good surface layer can be formed even when the basis weight of the surface layer is small.

[0105] Examples of the compatibilizer include styrene-butadiene copolymers, styrene-isoprene copolymers and styrene-based elastomers, such as hydrogenated products of these copolymers. The copolymer is preferably a block copolymer.

[0106] Based on 100 parts by weight of the polyethylene-based resin PE4, the polystyrene-based resin and the compatibilizer in total, the content of the compatibilizer in the mixed resin R4 is preferably 1-20 parts by weight. The lower limit of the content is more preferably 2 parts by weight, and the upper limit thereof is more preferably 15 parts by weight, and even more preferably 10 parts by weight.

[0107] The multilayer foam sheet of the present invention has higher rigidity than conventional foam sheets because the mixed resin R4 constituting the surface layer thereof contains a predetermined amount of polystyrene-based resin. In addition, the multilayer foam sheet is excellent in traceability during, for example, vacuum suction. Therefore, even when the thickness is thin, the foam sheet can be handled in the same manner as conventional thick sheets. When a compatibilizer is present in the mixed resin R4, in the mixed resin R4, the dispersibility of the polystyrene-based resin in the polyethylene-based resin PE4 is improved, so that the foam sheet has more improved operability, such as rigidity.

[0108] Next, various physical properties of the multilayer foam sheet of the present invention will be described.

[0109] The basis weight of the entire multi-layer foam sheet of the present invention is preferably 5-100 g / m 2 , more preferably 10-90 g / m 2 , and more preferably 20-80 g / m 2 , and particularly preferably 25-50 g / m 2 When the basis weight of the multilayer foam sheet is within this range, the balance between its lightness and mechanical properties is good.

[0110] The weight B3 of the intermediate layer 3 is preferably 1-10 g / m 2 When the weight of the middle layer B3 is 1 g / m 2 When the surface resistivity of each part is less than 1.5 g / m, the change of the antistatic property (surface resistivity) in each part is small. From this point of view, the quantitative B3 is more preferably 1.5 g / m 2 More preferably, it is 1.8 g / m 2 In addition, when the quantitative B3 is 10 g / m 2 When the weight B3 of the intermediate layer is less than 8 g / m2, the migration of low molecular weight components derived from the polymer antistatic agent is more likely to be suppressed, the closed cell content of the foam sheet can be further increased, and the stiffness of the foam sheet can be further improved. From this point of view, the weight B3 of the intermediate layer is more preferably 8 g / m2. 2 Below, more preferably 6 g / m 2 the following.

[0111] The weight B4 of the surface layer 4 is preferably 0.5-10 g / m 2 When the quantitative B4 is within this range, the exudation of low molecular weight components derived from the polymer antistatic agent can be more effectively suppressed and good antistatic properties can be more reliably exhibited. In order to achieve both the suppression of exudation and the development of antistatic properties in a well-balanced manner, the lower limit of the quantitative B4 is more preferably 0.8 g / m 2 , and more preferably 1.0 g / m 2 The upper limit of the quantitative B4 is more preferably 8 g / m 2, more preferably 5 g / m 2 , particularly preferably 3 g / m 2 .

[0112] Preferably, the ratio B4 / B3 of the quantitative B4 of the surface layer to the quantitative B3 of the intermediate layer is 0.05-10, more preferably 0.1-3, still more preferably 0.2-2, and particularly preferably 0.3-1.5. When the ratio B4 / B3 is within the above range, it is possible to achieve both the inhibition of the transfer of the low molecular weight components derived from the polymer antistatic agent and the antistatic properties in a more balanced manner.

[0113] The weight of the resin layer 5 (the sum of the weight of the surface layer B4 and the weight of the intermediate layer B3) is preferably 20 g / m 2 When the weight of the resin layer is within this range, the lightness of the foam sheet may not be adversely affected, and the cushioning properties required for use as a backing paper, etc. may also be ensured. In addition, by laminating the resin layer 5 (intermediate layer 3 and surface layer 4) on the foam layer 2 by coextrusion as described below, a foam layer 2 having a good cell structure can be formed. Therefore, the weight of the resin layer is more preferably 15 g / m 2 Below, more preferably 10 g / m 2 Below, particularly preferably 8 g / m 2 On the other hand, in consideration of the appropriate rigidity when used as a backing paper, etc., the lower limit of the basis weight of the resin layer 5 is preferably 1 g / m 2 , more preferably 2 g / m 2 .

[0114] The above-mentioned quantitative is the quantitative of the resin layer 5 (surface layer 4 and middle layer 3) provided on one of the two sides of the foam layer 2. Among the two resin layers, the two surface layers and the two middle layers, although they may be different from each other, it is preferred that the quantitative of one layer is the same as the quantitative of the other corresponding layer.

[0115] From the viewpoint of better balancing the inhibition of the migration of low molecular weight components derived from the polymer antistatic agent and the antistatic property, it is most preferred that 2 The amount of the polymer antistatic agent in the intermediate layer is 0.15 g or more and 2 g or less, and the quantitative B4 [g / m 2 ] and the content of polymer antistatic agent A [g / m 2 ] ratio (B4 / A) is 1 or more and 30 or less, and the quantitative B4 of the surface layer is 0.5 g / m 2 Above and 10 g / m 2 the following.

[0116] The apparent density of the multilayer foam sheet 1 of the present invention is preferably 10-300 kg / m 3When the apparent density of the foam sheet is within the above range, the foam sheet has an excellent balance between mechanical properties such as high stiffness, light weight and cushioning properties. From this point of view, the lower limit of the apparent density is more preferably 15 kg / m 3 , and more preferably 20 kg / m 3 On the other hand, the upper limit of the apparent density is more preferably 200 kg / m 3 , and more preferably 100 kg / m 3 .

[0117] The total thickness of the foam sheet is preferably 0.05-3 mm, more preferably 0.1-2 mm, still more preferably 0.3-1.8 mm, particularly preferably 0.5-1.5 mm. When the thickness of the foam sheet is within this range, the balance between cushioning properties and flexibility is good, and in addition, rigidity becomes better.

[0118] In the present invention, the thickness, basis weight, and apparent density of the multilayer foam sheet are measured as follows.

[0119] First, the multilayer foam sheet is cut vertically (i.e., in the thickness direction) along its transverse direction (i.e., the direction perpendicular to the extrusion direction) to obtain a rectangular test piece having a length [mm] equal to the entire width of the sheet and a width of 100 mm. Similar operations are repeated at different positions on the foam sheet to obtain a total of 5 test pieces. The thickness of each test piece is measured at 1 cm intervals in the transverse direction of the foam sheet. The arithmetic mean of the thickness values ​​obtained is the thickness [mm] of the multilayer foam sheet. In addition, the weight [g] of each test piece is measured. The measured weight is divided by the area [m 2 ] (i.e., the width of the sheet [m] × 100 mm (0.1 m)). The arithmetic mean of the five values ​​obtained is the basis weight [g / m 2 ]. The apparent density of the multilayer foam sheet [kg / m 3 ] The quantitative [g / m 2 ] divided by the thickness [m] of the foam sheet obtained above and converted into appropriate units.

[0120] The quantification of middle layer 3 and surface layer 4 can be determined by the thickness of each layer and the density of the resin composition constituting each layer. More specifically, multilayer foam sheet is cut along its horizontal vertical (i.e. in thickness direction), and vertical cross section is taken at ten horizontally equally spaced positions on each side of foam sheet. On each of ten (enlarged) photos of each side of cutting foam sheet, the thickness of each in middle layer and surface layer is measured at intervals of every 1cm (true length) in its transverse direction. The arithmetic mean of the measured thickness values ​​of middle layer and surface layer are respectively represented by the thickness of the middle layer and surface layer on the corresponding sides of foam sheet. The quantification of middle layer and surface layer can be calculated by multiplying their thickness by the density (converted with appropriate units) of its resin composition. As used herein, term "resin composition" is expected to include not only polyethylene resin component, but also other polymer components and inorganic components used in each layer.

[0121] Alternatively, the weight of the intermediate layer and the surface layer can be determined based on the discharge amount of each layer when manufacturing the multilayer foam sheet. Specifically, the weight of the intermediate layer B3 [g / m 2 ] can be calculated by the following equation:

[0122] B3 = [1000×X / (L×W)]

[0123] Where X is the discharge of the middle layer [kg / hour], L is the take-up speed of the foam sheet [m / hour], and W is the width of the foam sheet [m].

[0124] The quantitative B4 of the surface layer can be calculated by the following equation:

[0125] B4 = [1000×Y / (L×W)]

[0126] wherein Y is the discharge amount of the surface layer [kg / hour], and L and W are as defined above.

[0127] In consideration of the surface protection, cushioning properties, appropriate sliding properties, rigidity, etc. of the products to be packaged therewith, the closed cell content of the multilayer foam sheet of the present invention is preferably 20% or more, more preferably 30% or more, more preferably 40% or more, particularly preferably 50% or more, and most preferably 60% or more. The upper limit of the closed cell content is not particularly limited, but is generally 90%. In particular, when the basis weight of the foam sheet is 25-50 g / m 2 When the content of closed cells is within the range of , from the viewpoint of maintaining good elasticity, the closed cell content is preferably 40% or more.

[0128] The closed cell content is measured according to ASTM-D2856-70, Procedure C. Specifically, the true volume Vx of the multilayer foam sheet (cut sample) is measured using an air comparative pycnometer model 930 of Toshiba Beckman Inc. Using the obtained Vx, the closed cell content S (%) is calculated by the formula shown below. As the cut sample for measurement, a plurality of samples each having a size of 25 mm×25 mm×the thickness of the multilayer foam sheet are cut out from the multilayer foam sheet, and the obtained samples are stacked to obtain a cut sample of 25 mm×25 mm×about 20 mm for measurement.

[0129] S (%) = (Vx - W / ρ)×100 / (Va - W / ρ)

[0130] in

[0131] Vx represents the actual volume (cm2) of the cut sample measured by the above method. 3 ), which corresponds to the sum of the volume of the resin constituting the cut sample and the total volume of all closed cells in the cut sample,

[0132] Va represents the apparent volume of the cut sample measured from the outer dimensions of the cut sample (cm 3 ),

[0133] W is the total weight of the cut sample used for measurement (g); and

[0134] ρ is the density of the resin composition constituting the multilayer foam sheet (g / cm 3 ), which is determined after defoaming the multilayer foam sheet.

[0135] Next, a method for producing the multilayer foam sheet of the present invention will be described.

[0136] The multilayer foam sheet of the present invention can be produced by known procedures. As its typical preferred procedure, for example such a method can be mentioned, wherein in a coextrusion die, the melt for forming the intermediate layer and the melt for forming the surface layer are laminated in this order to the two sides of the foamable melt for forming the foam layer, and the laminated material obtained is coextruded to foam and expand the foamable melt, thereby producing the multilayer foam sheet. However, the multilayer foam sheet can also be manufactured as follows: by using a coextrusion die, the melt for forming the intermediate layer and the melt for forming the surface layer are laminated to obtain a resin layer with a multilayer structure, and then the resin layer is laminated on each side of the two sides of the foam sheet (foam layer) prepared separately, wherein the intermediate layer faces the foam sheet.

[0137] The multilayer coextrusion method includes (1) a method of coextruding into a sheet using a flat die to form a multilayer foam sheet, and (2) a method of coextruding into a tubular form using an annular die to produce a tubular multilayer foam body, and then cutting the obtained tubular multilayer foam body along the extrusion direction to obtain a multilayer foam sheet. Among the above methods, the multilayer coextrusion method using an annular die can be preferably used because a wide multilayer foam sheet with a width of 1000 mm or more can be easily obtained.

[0138] The coextrusion method using an annular die will be described in detail below.

[0139] First, polyethylene resin PE2 and additives such as cell control agents added as required are supplied to an extruder, and kneaded under heating, and then a physical foaming agent is injected therein. The contents in the extruder are further kneaded to obtain a foamable melt M2 for forming a foam layer. Meanwhile, polyethylene resin PE3, polymer antistatic agent and polyethylene glycol (added as required) are supplied to another extruder, and kneaded under heating to obtain a melt M3 for forming an intermediate layer. In addition, polyethylene resin PE4, polyethylene resin (C) etc. are supplied to another extruder, and kneaded under heating to obtain a melt M4 for forming a surface layer. The foamable melt M2, melt M3 and melt M4 obtained are introduced into a co-extrusion annular die, wherein the melt M3 for the intermediate layer is laminated on both sides of the foamable melt M2 flowing in a tubular shape. In addition, the melt M4 for the surface layer is laminated on both sides thereof. Then the resulting laminate is extruded in the atmosphere and foamed to form a tubular foam. The tubular foam is cut while being pulled along a widening device, such as a mandrel, to obtain a multi-layer foam sheet.

[0140] As described above, the two resin layers 5 may have the same or different configurations. Therefore, the composition (resin component, type and amount of additives, etc.) of the melt M3 used for one of the two intermediate layers 3 may be the same or different from that of the other intermediate layer. Similarly, the composition (resin component, type and amount of additives, etc.) of the melt M4 of one of the two surface layers 4 may be the same or different from that of the other surface layer.

[0141] When the multilayer foam sheet of the present invention is manufactured by a lamination coextrusion method, the melt flow rate (MFR) of the polyethylene-based resin PE2 is preferably 0.1-1.5 g / 10 min, since a decrease in closed cell content and a decrease in thickness recovery properties of the foam layer can be effectively suppressed.

[0142] When the foam sheet of the present invention is produced by a lamination coextrusion method, the melt viscosity of the melt M4 used for the surface layer tends to be high due to the presence of polystyrene-based resins therein, and the shear heat generation in the mold tends to be large. As a result, due to the generation of shear heat, the closed-cell content and thickness recovery of the foam layer may be easily reduced. On the other hand, when the melt flow rate (MFR) of the polyethylene-based resin PE2 in the foam layer is 0.1-1.5g / 10 min, due to the high melt viscosity of the foamable melt M2, the influence of shear heat generation is alleviated. In addition, when the MFR of the polyethylene-based resin PE2 is within the above range, the cell structure is considered to be easily maintained.

[0143] Generally, the thickness of a polyethylene-based resin foam sheet tends to decrease as the air in the cells is released therefrom immediately after its production. This decrease in thickness can usually be recovered by leaving the foam sheet at a predetermined temperature for a predetermined time (aging), but there are cases where the thickness may not increase for some reasons even when it is aged. This phenomenon that the thickness cannot be recovered is called a decrease in thickness recovery properties. One of the reasons for the decrease in recovery properties is believed to be a decrease in closed cell content.

[0144] When the resin layers are laminated by coextrusion, it is preferred that the MFR of the polyethylene-based resin PE3 and the polyethylene-based resin PE4 are each equal to or greater than the MFR of the polyethylene-based resin PE2 because the film-forming property of the resin layers is improved.

[0145] Preferably, volatile plasticizer is added to each melt M3 for the intermediate layer and melt M4 for the surface layer. As volatile plasticizer, a volatile plasticizer that has the function of reducing the melt viscosity of the melt and volatilizes from the intermediate layer and the surface layer after forming the resin layer (intermediate layer and surface layer) and is not present in the intermediate layer and the surface layer is used. By incorporating volatile plasticizer into each melt, when co-extruding the foam sheet, the extrusion temperature of each melt M3 for the intermediate layer and melt M4 for the surface layer can become close to the extrusion resin temperature of the foamable melt M2 for the foam layer, and in addition, the melt stretchability of the intermediate layer and the surface layer resin layer in the molten state can be significantly improved. Therefore, the foam cells of the foam layer are unlikely to be destroyed by the heat of the resin layer (intermediate layer and surface layer) when foaming, and in addition, during its foaming, the resin layer can be easily stretched after the foam layer is stretched.

[0146] As the volatile plasticizer, one or more selected from aliphatic hydrocarbons or alicyclic hydrocarbons having 3 to 7 carbon atoms, aliphatic alcohols having 1 to 4 carbon atoms, and aliphatic ethers having 2 to 8 carbon atoms are preferably used. When a low-volatile substance such as a so-called lubricant is used instead of a volatile plasticizer, the lubricant may remain in the resin layer and contaminate the surface of the article to be packaged. On the contrary, a volatile plasticizer is preferred because it effectively plasticizes the resin in the resin layer and because it hardly remains in the obtained resin layer.

[0147] The boiling point of the volatile plasticizer is preferably 120° C. or lower, more preferably 80° C. or lower, because it is easy to volatilize from the resin layer. When the boiling point of the volatile plasticizer is within the above range, and when the foam sheet obtained by coextrusion is left to stand after coextrusion, the volatile plasticizer volatilizes spontaneously, and the volatile plasticizer is removed from the resin layer (intermediate layer and surface layer) by heat retained therein immediately after coextrusion or by subsequent gas permeation at room temperature. The lower limit of the boiling point of the volatile plasticizer is generally -50° C.

[0148] The volatile plasticizer is preferably added to each of the melts M3 and M4 in an amount of 5 to 50 parts by weight, based on 100 parts by weight of each melt.

[0149] In addition, in the melts M3 and M4, various additives may be added to the resins constituting these melts as long as the purpose of the present invention is not adversely affected. Examples of various additives include antioxidants, heat stabilizers, weathering agents, ultraviolet absorbers, flame retardants, fillers, and antibacterial agents. In that case, the amount added is appropriately determined according to the purpose and effect of the additive, but is preferably 10 parts by weight or less, more preferably 5 parts by weight or less, and particularly preferably 3 parts by weight or less based on 100 parts by weight of each melt.

[0150] Examples of physical foaming agents added to the foamable melt M2 for the foam layer include organic physical foaming agents such as aliphatic hydrocarbons (e.g., propane, n-butane, isobutane, n-pentane, isopentane, n-hexane and isohexane), alicyclic hydrocarbons (e.g., cyclopentane, cyclohexane), chlorinated hydrocarbons (e.g., methyl chloride and ethyl chloride), fluorocarbons (e.g., 1,1,1,2-tetrafluoroethane and 1,1-difluoroethane) and inorganic physical foaming agents such as nitrogen, carbon dioxide, air and water. In some cases, decomposition-type foaming agents such as azodicarbonamide may also be used. Two or more of the above-mentioned physical foaming agents may be used in combination. Among them, organic physical foaming agents are preferred because they are excellent in compatibility with polyethylene resins and in foamability, and among them, those containing n-butane, isobutane or a mixture thereof as the main component are preferred.

[0151] The amount of the physical blowing agent added is controlled according to the type of the blowing agent and the desired apparent density. In order to obtain a multilayer foam sheet having the above-mentioned apparent density range using, for example, a mixed butane consisting of 30 wt% of isobutane and 70 wt% of normal butane as a blowing agent, the amount of the mixed butane added is preferably 3-30 wt%, more preferably 4-20 wt%, and even more preferably 6-18 wt%, per 100 wt% of the base polymer.

[0152] Cell control agents are usually added to the foamable melt M2 as its main additive. As cell control agents, organic or inorganic types can be used. As inorganic cell control agents, metal borates (such as zinc borate, magnesium borate and borax), sodium chloride, aluminum hydroxide, talc, zeolite, silicon dioxide, calcium carbonate and sodium bicarbonate can be mentioned, for example. As organic pore control agents, 2,2-methylene bis (4,6-tert-butylphenyl) sodium phosphate, sodium benzoate, calcium benzoate, aluminum benzoate and sodium stearate can be mentioned. In addition, a combination of citric acid and sodium bicarbonate and a combination of an alkali metal salt of citric acid and sodium bicarbonate can also be used as a cell control agent. Two or more of these cell control agents can be used in combination. For every 100 parts by weight of base polymer, the addition amount of the cell control agent is preferably 0.01-3 parts by weight, more preferably 0.03-1 parts by weight.

[0153] As the production apparatus such as an annular die and an extruder, known apparatuses which have been conventionally used in the field of extrusion foaming can be used.

[0154] The multilayer foam sheet of the present invention is excellent in cushioning properties and in antistatic properties, and the amount of low molecular weight components that can be transferred to the product packaged therewith is extremely low. Therefore, the foam sheet can be suitably used as a packaging material for electronic devices and a backing paper for glass plates such as liquid crystal panels.

[0155] Example:

[0156] The present invention will be described in more detail based on Examples. However, the present invention is not limited to these Examples.

[0157] The polyethylene-based resin, polystyrene-based resin, polymer antistatic agent, compatibilizer and cell control agent used in the Examples and Comparative Examples are as follows.

[0158] Polyethylene-based resin:

[0159] (1) Abbreviation "LDPE1": Low-density polyethylene "NUC8321" (density 922 kg / m 3 , MFR 2.4 g / 10 min, melting point 112°C, melt viscosity 818 Pa / s (measurement temperature 190°C), melt tension 64mN);

[0160] (2) Abbreviation "LDPE2": Low-density polyethylene "NS-1s" (density 922 kg / m 3 , MFR 0.4 g / 10 min, melting point 110°C, melt viscosity 1,468 Pa / s (measurement temperature 190°C), melt tension 199mN).

[0161] Polystyrene-based resins:

[0162] (1) Abbreviation "GPPS1": General purpose polystyrene "680" (density 1,050 kg / m 3 , MFR 7.0 g / 10 min, Vicat softening temperature 98°C, melt viscosity 927 Pa / s (measurement temperature 200°C), melt tension 73mN).

[0163] Polymer antistatic agent:

[0164] (1) Abbreviation "LMP": polyether-polyolefin block copolymer "PERECTRON LMP" manufactured by Sanyo Chemical Industries, Ltd. (MFR 17 g / 10 min, melting point 117°C, surface resistivity 2.0×10 7 Ω);

[0165] (2) Abbreviation "SD100": Vinyl potassium ionomer resin "ENTILA SD100" manufactured by Mitsui-DuPont Polychemicals Company Ltd. (MFR 5 g / 10 min, melting point 92°C, surface resistivity 1.0×10 7 Ω).

[0166] Compatibilizer:

[0167] (1) Abbreviation “SEBS1”: hydrogenated styrene-based thermoplastic elastomer “TUFTEC H1041” manufactured by Asahi Kasei Corporation, rubber content 70%.

[0168] Cell control agent: A cell control agent masterbatch containing 20% ​​of talc (talc "HIGH FILLER #12" manufactured by Matsumura Sangyo Co., Ltd.) added to 80% by weight of low-density polyethylene ("LA500M" manufactured by Japan Polyethylene Corporation) was used.

[0169] equipment:

[0170] A multi-layer foam sheet manufacturing apparatus was used having the following extruder and die.

[0171] Extruder for forming the foam layer: Single extruder with a barrel inner diameter of 115 mm (first extruder),

[0172] Extruder for forming the middle layer: extruder with a barrel inner diameter of 65 mm (second extruder),

[0173] Extruder for forming the surface layer: an extruder having a barrel inner diameter of 50 mm (the third extruder),

[0174] Die: Annular die for coextrusion with an outlet diameter of 96 mm.

[0175] Examples 1-9 and Comparative Examples 1-6

[0176] The foam sheet with a five-layer structure consisting of resin layer (surface layer / middle layer) / foam layer / resin layer (middle layer / surface layer) (Examples 1-9 and Comparative Examples 4-6) and the foam sheet with a three-layer structure consisting of surface layer / foam layer / surface layer (Comparative Examples 1-3) were produced by the following method. The composition of the layers constituting each multilayer foam sheet is shown in Table 1 and Table 2. Since the composition and physical properties of the two layers (resin layer, surface layer and middle layer) provided on both sides of the foam layer of each multilayer foam sheet are the same, only the composition and physical properties of one layer are shown in the following table. In Table 1 and Table 2, "%" and "parts" are "weight %" and "weight parts" respectively.

[0177] The polyethylene resin PE2 of the kind and addition amount shown in Table 1 (Example) and Table 2 (Comparative Example) and 2 parts by weight of talc masterbatch as a cell control agent per 100 parts by weight of the polyethylene resin PE2 were fed to the first extruder and kneaded at about 200° C., and then isobutane in the amount shown in Table 1 and Table 2 was injected therein as a physical foaming agent. The contents were further kneaded. The kneaded material was adjusted to the extrusion resin temperature shown in Table 3 (Example) and Table 4 (Comparative Example) with the first extruder to form a melt M2 for a foam layer.

[0178] Meanwhile, polyethylene-based resin PE3 of the kind and amount shown in Tables 1 and 2, polymer antistatic agent of the kind and amount shown in Tables 1 and 2, and polyalkylene glycol of the kind and amount shown in Tables 1 and 2 were fed to the second extruder and kneaded at about 200° C., into which mixed butane (n-butane / isobutane=65 wt % / 35 wt %) as a volatile plasticizer was injected in the amount shown in Tables 1 and 2. The contents were further kneaded and adjusted to the extrusion resin temperature shown in Tables 3 and 4 to form a melt M3 for the intermediate layer.

[0179] Meanwhile, further, the polyethylene-based resin PE4 of the type and amount shown in Table 1 and Table 2, the polystyrene-based resin of the amount shown in Table 1 and Table 2, the compatibilizer of the type and amount shown in Table 1 and Table 2, the polyalkylene glycol of the type and amount shown in Table 2 (only Comparative Examples 1 and 2), the polymer antistatic agent of the type and amount shown in Table 2 (only Comparative Examples 1-3) and 50% by weight of the talc masterbatch (only Comparative Example 2) are fed to the third extruder and kneaded at about 200°C, and the mixed butane (n-butane / isobutane=65% by weight / 35% by weight) of the amount shown in Table 1 and Table 2 is injected therein as a volatile plasticizer. The contents are further kneaded and adjusted to the extrusion resin temperature shown in Table 3 and Table 4 to obtain a melt M4 for the surface layer. The blending amount of the raw materials (excluding volatile raw materials) shown in Table 1 and Table 2 is the content thereof in the surface layer 4 (i.e., mixed resin R4) and the intermediate layer 3 (i.e., antistatic resin composition R3) constituting the obtained multilayer foam sheet.

[0180] The foamable melt M2 for foam layer, the melt M3 for the intermediate layer and the melt M4 for the surface layer are fed to the coextrusion annular die with the discharge amount shown in Table 3 (embodiment) and Table 4 (comparative example), wherein the melt M3 is merged and laminated on both the inner side and the outer side of the foamable melt M2, and further the melt M4 is merged and laminated on both the inner side and the outer side of each melt M3. The laminated material obtained is coextruded by annular die to obtain a tubular multilayer foam with a five-layer structure (three-layer structure in comparative examples 1-3, wherein there is no intermediate layer), wherein the intermediate layer is laminated and adhered to both the inner surface and the outer surface of the foam layer, and further, the surface layer is laminated and adhered to each intermediate layer. The extruded tubular multilayer foam was expanded on a tubular widening device having an outer diameter of 340 mm, and pulled at the pulling rate shown in Table 3 (Example) and Table 4 (Comparative Example) so that the basis weight (total basis weight) of the multilayer foam sheet was as shown in Table 5 (Example) and Table 6 (Comparative Example). At the same time, the extruded tubular multilayer foam was cut in the extrusion direction to obtain a multilayer foam sheet having a width of 1,050 mm. The obtained multilayer foam sheet was aged in an aging chamber at 40° C. for 24 hours, and then the following physical properties were measured.

[0181] Table 1

[0182]

[0183] Table 2

[0184]

[0185]

[0186] Table 3

[0187]

[0188] Table 4

[0189]

[0190] The physical properties of the multilayer foam sheets obtained in Examples and Comparative Examples were measured. The measurement results of Examples are shown in Table 5, and the measurement results of Comparative Examples are shown in Table 6.

[0191] Table 5

[0192]

[0193]

[0194] Table 6

[0195]

[0196]

[0197] The melting point of the polyethylene-based resin used in the examples and comparative examples is the melting peak temperature measured at a heating rate of 10°C / min, using condition (2) as the state adjustment of the test piece according to JIS K7121-1987. The Vicat softening temperature of the polystyrene-based resin is determined according to JIS K7206 (under the conditions of the test load including the A method and the heating rate of the heat transfer medium of 50±5°C / hour). The melt flow rate of the polyethylene-based resin and the polymer antistatic agent is measured under the conditions of 190°C and a load of 2.16 kg based on JIS K7210-1 (2014). The melt flow rate of the polystyrene-based resin is measured under the conditions of 200°C and a load of 5.0 kg based on JIS K7210-1 (2014).

[0198] The melt viscosity (η) was measured using a Capillograph 1D manufactured by Toyo Seiki Seisakusho Co., Ltd. Specifically, a cylinder with a cylinder diameter of 9.55 mm and a length of 350 mm and a nozzle diameter of 1.0 mm and a hole with a length of 10 mm were used. For polyethylene-based resins, the cylinder and hole were set at 190°C, while for polystyrene-based resins, the cylinder and hole were set at 200°C. 15 g of the measurement sample was loaded into the cylinder and allowed to stand for 4 minutes. The obtained molten sample was passed through the hole in the form of a line for 100 seconds. -1 The extrusion was carried out at a shear rate of 1000 rpm to measure the melt viscosity.

[0199] The melt tension was measured using a Capillograph 1D manufactured by Toyo Seiki Seisakusho Co., Ltd. Specifically, a cylinder with a cylinder diameter of 9.55 mm and a length of 350 mm and a nozzle diameter of 2.095 mm and a hole with a length of 8.0 mm were used. The cylinder and the hole were set at a temperature of 190°C. The required amount of sample was loaded into the cylinder and allowed to stand for 4 minutes. The obtained molten sample was extruded through the hole in the form of a line at a piston speed of 10 mm / min. The extruded line was placed on a tension detection pulley with a diameter of 45 mm and was wound onto a winding roller while increasing the winding speed from 0 mm / min to 200 mm / min at a constant rate over a period of 4 minutes. The maximum value of the tension of the wire strand before it is about to break was measured. Here, the reason for setting the time required for the winding speed to reach 200 m / min from 0 m / min to 4 minutes is to suppress the thermal degradation of the resin and improve the reproducibility of the obtained value. The above procedure was performed on 10 different samples. From the 10 measured values ​​obtained, the three largest values ​​and the three smallest values ​​were removed, and the arithmetic mean of the remaining four measured values ​​was taken as the melt tension (mN).

[0200] The tensile strength of the surface layer in Table 1 and Table 2 is a value measured as follows. First, a single screw extruder with L / D equal to 50 was used to melt-knead the raw material pellets having the same composition as the surface layer of each embodiment and comparative example at 200°C. Next, the kneaded material was extruded and formed into a film having a thickness of 2 mm, which was further punched into a dumbbell-shaped No. 1 to prepare a test piece. Using this test piece, the tensile strength (n = 5) was measured according to JIS K6767 (1999) as described above.

[0201] The measurement and evaluation of each physical property in Table 5 and Table 6 were performed as follows.

[0202] (1) Apparent density, basis weight and thickness of multi-layer foam sheets:

[0203] The apparent density, basis weight and thickness of the multilayer foam sheet are determined by the aforementioned method. First, the multilayer foam sheet is cut vertically (i.e., in the thickness direction) along its transverse direction (i.e., the direction perpendicular to the extrusion direction) to obtain a rectangular test piece with a length equal to the total width [mm] of the sheet and a width of 100 mm. The same operation is repeated at different positions on the foam sheet to obtain a total of 5 test pieces. The thickness of each test piece is measured at 1 cm intervals in the transverse direction of the foam sheet. The arithmetic mean of the thickness values ​​obtained is defined as the thickness [mm] of the multilayer foam sheet. The weight [g] of each test piece is also measured. The measured weight is divided by the area [m 2] (i.e., the width of the sheet [m] × 100 mm (0.1 m)). The arithmetic mean of the five values ​​obtained is defined as the basis weight [g / m 2 By the quantitative [g / m 2 ] divided by the thickness [m] of the foam sheet obtained above to determine the apparent density [kg / m 3 ] (with appropriate unit conversions).

[0204] (2) Quantity of surface layer and middle layer and thickness of resin layer:

[0205] The basis weight of the surface layer and the middle layer is calculated from the discharge amount of each of the surface layer and the middle layer (i.e., the discharge amount of melt M4 for the surface layer and the discharge amount of melt M3 for the middle layer). Specifically, from the discharge amount X [kg / hour] of each side of the middle layer, the discharge amount Y [kg / hour] of each side of the surface layer, the width W [m] of the multilayer foam sheet, and the winding speed L [m / hour], the basis weights [g / m 2 ]. In addition, the sum of the intermediate layer and the surface layer is taken as the quantitative amount of the resin layer. By the way, since the multilayer foam sheet is manufactured under such conditions that the quantitative amount of the surface layer and the intermediate layer on one surface side thereof is the same as the quantitative amount of the surface layer and the intermediate layer on the other surface side thereof, only the quantitative amount of one side thereof is shown in Tables 5 and 6.

[0206] The weight of the middle layer B3 [g / m 2 ] = [1000×X / (L×W)];

[0207] Surface layer weight B4 [g / m 2 ] = [1000×Y / (L×W)].

[0208] (3) Evaluation of antistatic properties (measurement of surface resistivity):

[0209] Three test pieces were cut from the transverse center and both ends of the multilayer foam sheet, each of which was 100 mm long, 100 mm wide, and equal to the thickness of the multilayer foam sheet. Each test piece was left to stand for 24 hours in an atmosphere with a temperature of 23 ° C and a relative humidity of 50%. Then, according to JIS K6271 (2001), a voltage of 500 V was applied to the test piece at an atmosphere of 23 ° C and a relative humidity of 50%, and the surface resistivity of the test piece was measured after the voltage was applied for 1 minute. The surface resistivity was measured on both sides of the test piece (3 test pieces × both sides: 6 times in total). The arithmetic mean of the measured values ​​obtained was taken as the surface resistivity. As a measuring instrument, "TR8601" manufactured by Takeda Riken Kogyo Co., Ltd. was used.

[0210] Based on the measured value of the surface resistivity, the antistatic property of the multilayer foam sheet was evaluated according to the following criteria.

[0211] A: Surface resistivity is 1.0×10 12 Ω or less;

[0212] B: Surface resistivity higher than 1.0×10 12 Ω and 1.0×10 13 Ω or less;

[0213] C: Surface resistivity higher than 1.0×10 13 Ω.

[0214] (4) The closed cell content of the multilayer foam sheet is measured by the aforementioned method. First, according to Procedure C of ASTM-D2856-70, the true volume Vx of the multilayer foam sheet (cut sample) is measured using an air comparative pycnometer model 930 of Toshiba Beckman Co., Ltd. Using the obtained Vx, the closed cell content S (%) is calculated by the formula shown below. As a cut sample for measurement, a plurality of samples are cut from the multilayer foam sheet, each sample having a thickness of 25 mm × 25 mm × equal to the thickness of the multilayer foam sheet, and the obtained samples are stacked to obtain a cut sample with a size of 25 mm × 25 mm × about 20 mm for measurement.

[0215] S (%) = (Vx - W / ρ)×100 / (Va - W / ρ)

[0216] in

[0217] Vx represents the actual volume (cm2) of the cut sample measured by the above method. 3 ), and corresponds to the sum of the volume of the resin constituting the cut sample and the total cell volume of the closed-cell portion in the cut sample;

[0218] Va is the apparent volume (cm) of the cut sample calculated from the outer dimensions of the cut sample used for measurement. 3 );

[0219] W is the total weight of the cut sample used for measurement (g); and

[0220] ρ is the density (g / cm2) of the resin composition constituting the multilayer foam sheet obtained by defoaming the multilayer foam sheet. 3 ).

[0221] (5) Anti-glass contamination test

[0222] Glass for liquid crystal panels was used as the article to be packaged. 10 sheets of glass and 11 sheets of multilayer foam sheets were stacked to form a glass stack. The haze (1) of the glass stack in the thickness direction (glass stacking direction) was measured using "NDH2000" manufactured by Nippon Denshoku Kogyo Co., Ltd. Then, each glass was pressed into contact with the sample (foam sheet obtained in the examples and comparative examples) and allowed to stand for 168 hours at a temperature of 60°C and a relative humidity of 90%, while applying 50 g / cm 2 The surface pressure load of the multilayer foam sheet is measured. The sample is then removed from the glass. 10 pieces of the resulting glass are stacked, and the haze (2) of the glass stack is measured in the same manner as the haze (1). The haze value (1) is subtracted from the haze value (2) to obtain the change in haze (the haze (%) of the glass after the test minus the haze (%) of the glass before the test). The anti-pollution properties of the multilayer foam sheet are evaluated according to the following criteria. The smaller the haze change, the lower the transfer of the low molecular weight components contained in the polymer antistatic agent of the multilayer foam sheet to the glass.

[0223] A: The change in haze is less than 1

[0224] B: The haze change is 1 or more and less than 1.5

[0225] C: Haze change is 1.5 or more and less than 2.5

[0226] D: The amount of change in haze is 2.5 or more.

[0227] (6) Evaluation of sliding properties: static friction

[0228] Static friction was measured by a method according to JIS K7125 (1999). First, six 50 mm × 50 mm square test pieces were cut from randomly selected portions of the multilayer foam sheet so that one side of each test piece was aligned with the extrusion direction of the multilayer foam sheet. Next, the test pieces were placed in an atmosphere of 23°C and 50% humidity for 24 hours to condition the state of the test pieces. Then, each test piece was fixed to a bottom surface having a size of 50 mm × 50 mm and a weight of 125 g (5 g / cm 2 ) and placed on a slide glass (manufactured by Matsunami Glass Industry Co., Ltd., product name "Standard Large Sized White Edge Polishing No. 2", product number S9112). Then, while aligning the extrusion direction of the multilayer foam sheet with the pulling direction of the measuring fixture, pull the measuring fixture in the horizontal direction at a speed of 100 mm / min so that the test piece slides on the slide glass. The first maximum point load at this time is defined as the static friction (N) of the test piece. Among the 6 test pieces, the static friction of 3 of the test pieces on the side in contact with the mandrel is measured, and the remaining three test pieces are measured on their opposite sides. The arithmetic mean (n = 6) of the static friction of each test piece is defined as the static friction (N) of the multilayer foam sheet under low load. The smaller the static friction, the better the sliding property.

[0229] Based on the measured value of static friction, the sliding property of the multilayer foam sheet was evaluated according to the following criteria.

[0230] A: static friction is less than 2 N;

[0231] B: static friction is greater than 2 N and less than 2.5 N;

[0232] C: static friction is greater than 2.5 N and less than 3 N;

[0233] D: Static friction is 3 N or more.

[0234] (7) Anti-adhesion properties: peel strength

[0235] Two test pieces of the multilayer foam sheet were cut to a size of 40 mm × 150 mm, overlapped one on the other, and applied with 33 g / cm 2 The test pieces were stored at 50°C for 168 hours while being loaded with a load of , and then the peel strength (gf) between the test pieces was measured at a test speed of 100 mm / min. Based on the measured values, the anti-blocking properties of the multilayer foam sheet were evaluated according to the following criteria. The lower the peel strength, the better the anti-blocking properties.

[0236] A: Peel strength is less than 15 gf;

[0237] B: Peel strength is 15 gf or more and less than 20 gf;

[0238] C: The peel strength is 20 gf or more.

[0239] (8) Evaluation of stiffness: droop

[0240] 10 measurement test pieces with a width of 200 mm and a length of 200 mm are cut out from the obtained multilayer foam sheet at 10 randomly selected positions so that the length direction of each test piece is consistent with the extrusion direction of the sheet. Each test piece obtained is fixed on the horizontal upper surface of the platform in a cantilever state, and the 100 mm length of the length direction of the test piece protrudes horizontally outward from its end. Therefore, the test piece droops downward from the upper surface of the platform due to its own weight. Measure the vertical distance from the plane of the upper surface of the platform to the lowest point of the drooping test piece. Such measurement is performed on each test piece. The arithmetic mean of the 10 measured values ​​obtained represents the droop (mm). The smaller the droop, the greater the rigidity.

[0241] A: The sag is less than 10 mm;

[0242] B: The sag is more than 10 mm and less than 15 mm;

[0243] C: The sag is more than 15 mm and less than 20 mm;

[0244] D: The sagging amount is 20 mm or more.

[0245] (9) Thickness recovery properties: Thickness recovery rate

[0246] First, the multilayer foam sheet just after extrusion was used as a test piece, and its thickness (initial thickness) was measured in the same manner as above. Next, the multilayer foam sheet was placed in an aging chamber at 40° C., stored and aged for 24 hours. The thickness of the multilayer foam sheet just after aging (thickness after aging) was measured, and the thickness recovery rate was determined by the following formula.

[0247] Thickness recovery rate (%) = ((thickness after aging - initial thickness) / initial thickness)) × 100

[0248] Based on the obtained recovery rate, the thickness recovery property of the multilayer foam sheet was evaluated according to the following criteria.

[0249] A: Thickness recovery rate is more than 20%

[0250] B: Thickness recovery rate is more than 10% and less than 20%

[0251] C: Thickness recovery rate is less than 10%

[0252] The thickness recovery property is an indicator of the rate of increase in thickness of a multilayer foam sheet just after production when it is subjected to aging. The thickness of a multilayer foam sheet is generally adjusted by the amount of foaming agent added, the winding speed, etc. Due to the dissipation of the foaming agent, the thickness of the multilayer foam sheet begins to decrease just after production. On the other hand, in a foam sheet having excellent thickness recovery properties, air replacement is performed during aging and its thickness increases. As a result, it is possible to obtain a foam sheet having a target thickness. When the thickness recovery property is not good, the thickness does not increase even after aging, and it may be difficult to obtain the target thickness in a stable manner.

[0253] The multilayer foam sheet material that obtains in embodiment 1-9 has the five-layer structure that is made of surface layer / middle layer / foam layer / middle layer / surface layer, and the resin layer that wherein is made of surface layer and middle layer is laminated and adheres to each side on foam layer both sides.Middle layer contains polymer antistatic agent, and the surface layer does not contain polymer antistatic agent.Therefore, foam sheet material has excellent antistatic property, and the transfer of low molecular weight component etc. is suppressed to extremely low level.In addition, because the surface layer contains the polystyrene-based resin of specific amount, operability (slipperiness, anti-blocking property and rigidity) is excellent.

[0254] Examples 6 to 9 are examples in which the blending amount of the polystyrene-based resin was increased compared with Example 4. The closed cell content of the obtained multilayer foam sheets was reduced, and as a result, the rigidity was slightly lower than that of Example 4. However, they could be used as liner paper.

[0255] Example 9 is the same example as Example 8, except that LDPE2 is used as the polyethylene-based resin of the foam layer. The obtained multi-layer foam sheet has excellent stiffness without having a reduced closed cell content as in Example 8.

[0256] Comparative Example 1 and Comparative Example 3 are examples in which a three-layer structure is formed without forming an intermediate layer, so that the surface layers thereof are respectively the same as the intermediate layers of Examples 4 and 5 and no polystyrene-based resin is added to the surface layers. Since a polymer antistatic agent is added to the surface layer, the obtained multilayer foam sheet shows insufficient anti-glass contamination properties. In addition, since no polystyrene-based resin is added to the surface layer, the sliding property and anti-blocking property are poor. In particular, the multilayer foam sheet of Comparative Example 1 in which an ionomer resin is incorporated into the surface layer as a polymer antistatic agent has reduced sliding property.

[0257] Comparative Example 2 is an example in which the composition of the surface layer in Comparative Example 1 is changed so that the surface layer is formed of 40 parts by weight of LDPE1, 50 parts by weight of talc masterbatch, and 10 parts by weight of a polymer antistatic agent. Compared with Comparative Example 1, although the slip and anti-blocking properties are improved, the obtained multilayer foam sheet shows significantly reduced anti-glass contamination properties.

[0258] Comparative Example 4 and Comparative Example 5 are examples in which a multilayer foam sheet having a five-layer structure was formed such that the surface layer consisted of only LDPE1, and the intermediate layer and the foam layer were respectively formed in the same manner as in Example 4 and Example 1. The obtained multilayer foam sheets were poor in sliding and anti-blocking properties.

[0259] Comparative Example 6 is an example in which a five-layer structure is formed as a whole so that the surface layer is formed of 40 parts by weight of LDPE1, 40 parts by weight of GPPS1 and 20 parts by weight of a compatibilizer, and the intermediate layer and the foam layer are formed in the same manner as in Example 1. The obtained multilayer foam sheet shows a significantly reduced closed cell content and greatly reduced rigidity. In addition, the thickness recovery property is also poor.

[0260] Explanation of symbols

[0261] 1: Multi-layer foam sheet

[0262] 2: Foam layer

[0263] 3: Middle layer

[0264] 4: Surface layer

[0265] 5: Resin layer

Claims

1. A polyethylene-based resin multilayer foam sheet comprising a foam layer and a resin layer provided on each of both sides of the foam layer, the resin layer has a multilayer structure including a surface layer located on the outermost surface side of the multilayer foam sheet and an intermediate layer located between the surface layer and the foam layer, The foam layer includes polyethylene resin PE2, in The middle layer is composed of an antistatic resin composition containing a polyethylene resin PE3 and a polymer antistatic agent. The surface layer is composed of a mixed resin containing polyethylene-based resin PE4 and polystyrene-based resin, and the quantitative B4 of the surface layer is 0.5g / m 2 Above and 10g / m 2 the following, The mixed resin is substantially free of polymer antistatic agent, which means that the content of polymer antistatic agent is 3 wt % or less, including 0, based on the weight of the mixed resin. The content of the polystyrene-based resin in the mixed resin is 3 wt % or more and 35 wt % or less, and the surface resistivity of the polyethylene-based resin multilayer foam sheet is 1×10 13 Ω or less. 2 . The polyethylene-based resin multi-layer foam sheet according to claim 1 , wherein a weight ratio of the polystyrene-based resin to the polyethylene-based resin PE4 in the mixed resin is 0.03 or more and 0.4 or less. 3 . The polyethylene-based resin multi-layer foam sheet according to claim 1 , wherein the content of the polystyrene-based resin in the mixed resin is 3% by weight or more and 12% by weight or less.

4. The polyethylene-based resin multi-layer foam sheet according to any one of claims 1 to 3, wherein the content of the polymer antistatic agent in the antistatic resin composition is 5 wt% or more and 25 wt% or less based on the total weight of the polyethylene-based resin PE3 and the polymer antistatic agent.

5. The polyethylene-based resin multi-layer foam sheet according to any one of claims 1 to 4, wherein the polymer antistatic agent is an ionomer resin.

6. The polyethylene-based resin multi-layer foam sheet according to claim 5, wherein the antistatic resin composition contains polyalkylene glycol, and wherein the content of the polyalkylene glycol is 0.3-6 parts by weight based on 100 parts by weight in total of the polyethylene-based resin PE3 and the polymer antistatic agent.

7. The polyethylene-based resin multi-layer foam sheet according to any one of claims 1 to 6, wherein each 1m 2 The content of the antistatic agent in the polymer of the intermediate layer is 0.15 g or more and 2 g or less, and the quantitative B4 [g / m 2 ] and every 1m 2 The content of the polymer antistatic agent in the intermediate layer is A[g / m 2 ] The ratio B4 / A is greater than or equal to 1 and less than or equal to 30.

8. The polyethylene-based resin multi-layer foam sheet according to any one of claims 1 to 7, wherein the polyethylene-based resin PE2 is a low-density polyethylene, and the polyethylene-based resin PE3 is a low-density polyethylene. 9 . The polyethylene-based resin multi-layer foam sheet according to claim 1 , wherein the polyethylene-based resin PE2 has a melt flow rate of 0.1 g / 10 min or more and 1.5 g / 10 min or less at a temperature of 190° C. and a load of 2.16 kg.

10. The polyethylene-based resin multi-layer foam sheet according to any one of claims 1 to 9, which has a closed cell content of 40% or more.

11. Use of the polyethylene-based resin multilayer foam sheet according to any one of claims 1 to 10 as a liner paper for a glass plate.

12. A method for producing the polyethylene-based resin multilayer foam sheet according to claim 1, wherein the surface resistivity of the polyethylene-based resin multilayer foam sheet is 1×10 13 Ω or less and having a multilayer structure in which a first surface layer, a first intermediate layer, a foam layer, a second intermediate layer, and a second surface layer are laminated in this order, the method comprising the following steps: providing a foamable melt M2 for forming the foam layer containing a polyethylene-based resin PE2 and a physical foaming agent, a melt M3 composed of an antistatic resin composition containing a polyethylene-based resin PE3 and a polymer antistatic agent for forming the first intermediate layer and the second intermediate layer, and a melt M4 composed of a mixed resin containing a polyethylene-based resin PE4 and a polystyrene-based resin and not containing a polymer antistatic agent for forming the first surface layer and the second surface layer, laminating the melts M4, M3, M2, M3 and M4 in this order in a die to form a laminated material, and co-extruding the laminated material from the die to expand the foamable melt M2, The polystyrene-based resin is contained in the mixed resin composition in an amount of 3 wt % or more and 35 wt % or less based on the weight of the mixed resin composition.

Citation Information

Patent Citations

  • Foamed sheet

    JP2008308695A

  • Lining paper

    CN109421345A

  • Laminated foam interleaf sheet for glass plates

    US20160311202A1